ChIPprimersDB: a public repository of verified qPCR primers for chromatin immunoprecipitation (ChIP). Issue Volume 47:Issue D1(2019) (7th September 2018) - Kurtenbach, Stefan; Reddy, Rohit; Harbour, J William
Abstract: Chromatin immunoprecipitation (ChIP) has ushered in a new era of scientific discovery by allowing new insights into DNA-protein interactions. ChIP is used to quantify enriched genomic regions using qPCR, and more recently is combined with next generation sequencing (ChIP-seq) to obtain a genome wide profile of protein binding sites. Nevertheless, ChIP-qPCR remains an integral component of this technology for quality control purposes, before the library preparation and sequencing steps. In addition, ChIP-qPCR remains more time- and cost-effective for many focused projects in which the DNA regions of interest are already known. However, the DNA oligonucleotide primers needed for ChIP-qPCR are more challenging to design than for other qPCR projects. Here, we present the first public repository for ChIP oligonucleotides that have been verified to perform well in ChIP-qPCR experiments. ChIPprimersDB was developed by manual screening of publications to ensure primer quality and provide additional specific information on the ChIP experiments where the primers have been used. In addition to the primer sequences, the database includes information about the antibody, cells and tissues used in the experiment, information on the experimental design, and a direct link to the original publication. The database is linked at https://umiamihealth.org/bascom-palmer-eye-institute/research/clinical-and-laboratory-research/ocular-oncology-laboratory/chip-primers and hosted at https://www.chipprimers.com/ .